Implementasi Manajemen Kesiswaan dalam Pembinaan Prestasi Non Akademik Siswa di SMPN 1 Percut Sei Tuan - Ryan Fazli Zulna; Muhammad Rifa’i (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: This research explores the implementation of student affairs management in supporting students’ achievements in non-academic domains at SMPN 1 Percut Sei Tuan. The study highlights how planning, execution, and evaluation of extracurricular activities are carried out to foster students' interests and talents. Employing a descriptive qualitative approach, the data were gathered through observations, interviews, and document analysis. The study found that planning takes place at the start of each academic term, beginning with identifying students’ preferences and abilities through an introductory orientation. Activities are then implemented based on coordinated schedules between students and activity coaches, with logistical and financial support provided by the school. Evaluations are conducted regularly during school coordination meetings to monitor progress and resolve implementation challenges. Although time constraints and overlapping with academic lessons are recurring issues, the school strives to maintain balance between formal and extracurricular learning. The findings also show that students have attained notable achievements in competitions across district, regional, and provincial levels. In summary, student management plays a vital role in advancing non-academic development. Key success factors include strategic planning, consistent coaching support, and continuous evaluation, all of which contribute to holistic student growth. Keywords: Student Management, Student Development, Non-Academic Achievements Abstrak: Penelitian ini membahas implementasi manajemen kesiswaan dalam mendukung pencapaian prestasi siswa di bidang non akademik di SMPN 1 Percut Sei Tuan. Kajian ini menitikberatkan pada proses perencanaan, pelaksanaan, dan evaluasi kegiatan ekstrakurikuler sebagai bentuk pengembangan minat dan bakat peserta didik. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, serta analisis dokumen. Temuan menunjukkan bahwa proses perencanaan dimulai pada awal tahun ajaran dengan mengenali potensi dan minat siswa melalui kegiatan orientasi ekstrakurikuler. Selanjutnya, kegiatan dilaksanakan berdasarkan kesepakatan jadwal antara siswa dan pembina, dengan dukungan fasilitas, pendanaan, dan sarana dari pihak sekolah. Evaluasi dilakukan secara rutin dalam forum koordinasi sekolah untuk mengkaji perkembangan serta mengatasi kendala pelaksanaan. Meskipun terdapat hambatan seperti terbatasnya waktu latihan dan benturan dengan jadwal pelajaran, sekolah tetap berupaya menjaga sinergi antara kegiatan akademik dan non akademik. Hasilnya, siswa berhasil meraih prestasi di berbagai kompetisi tingkat kecamatan, kabupaten, hingga provinsi. Secara keseluruhan, manajemen kesiswaan terbukti memiliki peran strategis dalam mendukung pengembangan potensi siswa secara non akademik. Faktor kunci keberhasilan mencakup perencanaan yang sistematis, dukungan pembina yang berkelanjutan, serta proses evaluasi yang konsisten dalam membina karakter dan kompetensi siswa secara menyeluruh. Kata kunci: Manajemen Kesiswaan,Pembinaan Siswa,Prestasi Non-Akademik